2020
DOI: 10.1021/acs.inorgchem.0c01949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pb Substitution in Sr2-xPbxGeSe4 on Crystal Structures and Nonlinear Optical Properties Predicted by DFT Calculations

Abstract: We investigated the Sr2‑xPb x GeSe4 series from 0 ≤ x ≤ 2 to study the impact of Pb on structure and properties. While the noncentrosymmetric (NCS) compounds γ-Sr2GeSe4 and α-Pb2GeSe4 have already been reported previously, the substitution variants Sr1.31Pb0.69GeSe4 (space group Ama2, a = 10.31220(1) Å, b = 10.39320(1) Å, c = 7.42140(1) Å) and Sr0.19Pb1.81GeSe4 (I4̅3d, a = 14.6177(3) Å) are introduced here for the first time. The experimentally determined optical band gaps decrease as predicted with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
(70 reference statements)
1
7
0
Order By: Relevance
“…10,11 On one hand, it can greatly improve the IR-NLO properties of chalcogenides, such as, Li 0.6 Ag 0.4 GaS 2 ( d eff = 1.1 × AgGaS 2 ) versus LiGaS 2 ( d eff = 0.4 × AgGaS 2 ), 12 Cu 5 Zn 0.5 P 2 S 8 ( d eff = 0.3 × AgGaS 2 ) versus Cu 3 PS 4 ( d eff = 0.03 × AgGaS 2 ), 13 and Sr 1.3 Pb 0.7 GeSe 4 ( d eff = 16 × SiO 2 ) versus Pb 2 GeSe 4 ( d eff = 2 × SiO 2 ). 14 On the other hand, it can realize centrosymmetric (CS)-to-NCS structure evolution in the chalcogenide system. Some classic examples include CS La 2 CuInS 5 versus NCS La 2 CuSbS 5 , 15 CS Ba 2 GaAsSe 5 versus NCS Ba 2 As 2 Se 5 , 16 CS BaGa 2 Se 4 versus NCS K 0.38 Ba 0.81 Ga 2 Se 4 , 17 CS K 2 Sb 4 S 7 versus NCS K 2 Ag 3 Sb 3 S 7 , 18 CS Rb 4 Hg 2 Ge 2 S 8 versus NCS (Na 3 Rb)Hg 2 Ge 2 S 8 , 19 CS SrGeO 3 versus NCS SrGeOSe 2 , 20 CS SnBr 2 versus NCS Sn 7 Br 10 S 2 , 21 and CS Rb 4 P 2 S 6 versus NCS RbBiP 2 S 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 On one hand, it can greatly improve the IR-NLO properties of chalcogenides, such as, Li 0.6 Ag 0.4 GaS 2 ( d eff = 1.1 × AgGaS 2 ) versus LiGaS 2 ( d eff = 0.4 × AgGaS 2 ), 12 Cu 5 Zn 0.5 P 2 S 8 ( d eff = 0.3 × AgGaS 2 ) versus Cu 3 PS 4 ( d eff = 0.03 × AgGaS 2 ), 13 and Sr 1.3 Pb 0.7 GeSe 4 ( d eff = 16 × SiO 2 ) versus Pb 2 GeSe 4 ( d eff = 2 × SiO 2 ). 14 On the other hand, it can realize centrosymmetric (CS)-to-NCS structure evolution in the chalcogenide system. Some classic examples include CS La 2 CuInS 5 versus NCS La 2 CuSbS 5 , 15 CS Ba 2 GaAsSe 5 versus NCS Ba 2 As 2 Se 5 , 16 CS BaGa 2 Se 4 versus NCS K 0.38 Ba 0.81 Ga 2 Se 4 , 17 CS K 2 Sb 4 S 7 versus NCS K 2 Ag 3 Sb 3 S 7 , 18 CS Rb 4 Hg 2 Ge 2 S 8 versus NCS (Na 3 Rb)Hg 2 Ge 2 S 8 , 19 CS SrGeO 3 versus NCS SrGeOSe 2 , 20 CS SnBr 2 versus NCS Sn 7 Br 10 S 2 , 21 and CS Rb 4 P 2 S 6 versus NCS RbBiP 2 S 6 .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 On one hand, it can greatly improve the IR-NLO properties of chalcogenides, such as, Li 0.6 Ag 0.4 GaS 2 (d eff ¼ 1.1 Â AgGaS 2 ) versus LiGaS 2 (d eff ¼ 0.4 Â AgGaS 2 ), 12 Cu 5 Zn 0.5 P 2 S 8 (d eff ¼ 0.3 Â AgGaS 2 ) versus Cu 3 PS 4 (d eff ¼ 0.03 Â AgGaS 2 ), 13 and Sr 1.3 Pb 0.7 GeSe 4 (d eff ¼ 16 Â SiO 2 ) versus Pb 2 GeSe 4 (d eff ¼ 2 Â SiO 2 ). 14 On the other hand, it can realize centrosymmetric (CS)-to-NCS structure evolution in the chalcogenide system. 22 Notably, compared to a large number of structural transformations achieved by single-site substitution mentioned above, examples of dual-site and multi-site substitution are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only two barium seleno-germanates have been reported, namely, Ba 2 GeSe 4 and Ba 2 Ge 2 Se 5 . , The former is a member of a diverse class of compounds with the general formula M II 2 TtQ 4 , where M II is either one or two different divalent cations, the tetrel Tt is a tetrahedrally coordinated cation such as Si, Ge, or Sn, and Q is a chalcogen atom such as S or Se. Exploratory search into M II – Tt – Q materials has been a reliable strategy for researchers to discover new compounds and new structure types. , Related materials are of interest in photovoltaic applications, including Ba 4 Ga 4 SnSe 12 and BaCu 2 SnS 4– x Se x . , Many of these compounds have been investigated for their nonlinear optical properties, in part because they are composed of noncentrosymmetric building blocks into the structure such as [ TtQ 4 ] 4– tetrahedra. Although neither Ba 6 Ge 2 Se 12 (space group P 2 1 / c ) nor Ba 7 Ge 2 Se 17 ( Pnma ) crystallizes in a noncentrosymmetric space group, they adopt new structure types. Stoichiometric analogues containing Sr, Sn, or S could not be synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, previous studies found significant NLO performance improvement in maternal materials by partial chemical substitution strategy, 24−28 for example, Li 0.6 Na 0.4 AsS 2 (E g = 1.9 eV; d ij = 30AgGaSe 2 ) versus LiAsS 2 (E g = 1.6 eV; d ij = 10AgGaSe 2 ), 26 Li 0.6 Ag 0.4 GaS 2 (E g = 3.4 eV; d ij = 1.1AgGaS 2 ) versus LiGaS 2 (E g = 4.2 eV; d ij = 0.4AgGaS 2 ), 27 and Sr 1.3 Pb 0.7 GeSe 4 (E g = 1.65 eV; d ij = 16SiO 2 ) versus Pb 2 GeSe 4 (E g = 1.42 eV; d ij = 2SiO 2 ). 28 However, the cases of d ij obviously improved based on aliovalent substitution are rare.…”
mentioning
confidence: 99%